A symptomatic gastric sarcoidosis and asymptomatic pulmonary sarcoidosis: a rare manifestation - Bikash Bhattarai; Amrendra Mandal; Jenny Lamichhane; Praveen Datar; Osama Mukhtar; Oday Alhafidh; Anton Lixon; Vijay Gayam; Danilo Enriquez; Joseph Quist; Frances Schmidt (Journal of Community Hospital Internal Medicine Perspectives, 2019)
Sarcoidosis is a granulomatous disease of unknown etiology which may present with systemic manifestations. The diagnosis of gastric sarcoidosis needs much effort to accomplish as it is exceedingly rare, and the treatment is usually recommended exclusively for symptomatic disease. Here, we present a case of gastric sarcoidosis in a 31-year old black female patient with symptoms of nausea and epigastric pain. A diagnosis of gastric sarcoidosis was mainly based on the presence of non-necrotizing granulomas on biopsy following esophagogastroduodenoscopy (EGD). She was treated with steroid with high dose at first, followed by a slow taper and the symptoms responded to the treatment.